1995
DOI: 10.1111/j.1558-5646.1995.tb05962.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovule Packaging in Stochastic Pollination and Fertilization Environments

Abstract: Abstract.-The modular morphology of plants has important consequences for reproductive strategies. Ovules are packaged in discrete structures (flowers) that usually vary stochastically in pollen capture and ovule fertilization, because of the vagaries of pollen transfer by external agents. Different ovule packaging schemes may use limited reproductive resources more or less effectively, so that some number of ovules per flower may be optimal, given the prevailing probabilities of ovule fertilization. I derive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 78 publications
4
92
1
3
Order By: Relevance
“…O aumento significativo da produção de frutos e da fecundidade após polinização cruzada manual em relação às condições naturais pode indicar limitação nos níveis de polinização natural (Stephenson 1981;Burd 1995). Tal limitação poderia ser pela escassez de polinizadores e/ou pelo transporte inadequado de pólen compatível, visto que 30% das espécies visitantes apresentaram comportamento pilhador.…”
Section: Polinização Cruzadaunclassified
“…O aumento significativo da produção de frutos e da fecundidade após polinização cruzada manual em relação às condições naturais pode indicar limitação nos níveis de polinização natural (Stephenson 1981;Burd 1995). Tal limitação poderia ser pela escassez de polinizadores e/ou pelo transporte inadequado de pólen compatível, visto que 30% das espécies visitantes apresentaram comportamento pilhador.…”
Section: Polinização Cruzadaunclassified
“…In contrast to variance reduction adaptations, most of the causes of diminishing returns after pollination involve female traits, including limited stigma capacity for pollen receipt, limited style capacity for transmission of pollen tubes, and limited ovule number. For example, Burd (1995) demonstrated theoretically that stochastic pollination may affect the evolution of production of "excess" ovules as a bet-hedging strategy to take advantage of occasional receipt of many pollen grains. In contrast, we found that greater ovule numbers generally aggravated variance limitation of seed production (compare curves in fig.…”
Section: Consequences Of Variation In Pollen Dispersalmentioning
confidence: 99%
“…Finally, stochastic variation in pollen removal, loss, and deposition as individual pollinators carry pollen from one flower or plant to others can arise from differing pollinator position and visit duration and from variation in stigma and anther positions (Lertzman and Gass 1983;Waser and Price 1984;Thomson 1986;Morris et al 1994;Cresswell 1999). Curiously, although the causes of variation in pollen dispersal are widely recognized, its ecological and evolutionary consequences have received little attention (although see Lertzman and Gass 1983;Galen and Rotenberry 1988;Burd 1995;Harder and Wilson 1998).…”
Section: Introductionmentioning
confidence: 99%
“…evolution toward self-compatibility or anemophily (wind pollination), can mitigate limitations of pollen dispersal (reviewed by Knight et al 2005). For example, Burd's (1995) ovule packaging model proposes the evolutionary adaptation of producing excess ovules per flower where pollen receipt is unpredictable, as a form of bet hedging. Here, the fitness benefits of ovule overproduction are greatest where stigmatic pollen loads are variable and the costs of ovules are low (Burd 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Burd's (1995) ovule packaging model proposes the evolutionary adaptation of producing excess ovules per flower where pollen receipt is unpredictable, as a form of bet hedging. Here, the fitness benefits of ovule overproduction are greatest where stigmatic pollen loads are variable and the costs of ovules are low (Burd 1995). Documentation of pollen limitation and low reproductive success in dioecious plants with abiotic pollination is rare, and is often investigated using species in areas of fragmented habitats or low plant density (e.g.…”
Section: Introductionmentioning
confidence: 99%